Longitudinally Extensive Transverse Myelitis with Mycobacterium Tuberculosis Infection - Sameena Majeed; Rifat Ullah; Muhammad Tahir; Majeed Ullah; Ayaz Ul Haq; Arif Hayat (Pakistan Journal of Medicine and Dentistry)
Background: Often encompassing three or more spinal segments, longitudinally extensive transverse myelitis (LETM) is a severe inflammatory disease of the spinal cord. The clinical presentation, pathophysiological processes, and therapeutic results in LETM connected to tuberculosis were investigated in this research.